2011
DOI: 10.1017/cbo9780511997587
|View full text |Cite
|
Sign up to set email alerts
|

The Modular Architecture of Grammar

Abstract: Modular grammar postulates several autonomous generative systems interacting with one another as opposed to the prevailing theory of transformational grammar where there is a single generative component – the syntax – from which other representations are derived. In this book Jerrold Sadock develops his influential theory of grammar, formalizing several generative modules that independently characterize the levels of syntax, semantics, role structure, morphology and linear order, as well as an interface system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
58
1
18

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(78 citation statements)
references
References 112 publications
1
58
1
18
Order By: Relevance
“…Moreover, total number of episodes and types of these episodes were found similar. This finding does not support the notion of "manic episodes are more frequent in women and depressive episodes are more frequent in men" (22). When current different findings were evaluated together, it can be suggested that biological mechanism which determines type and course of onset of disease and episode types is not affected by gender.…”
Section: Clinical Characteristicscontrasting
confidence: 56%
See 1 more Smart Citation
“…Moreover, total number of episodes and types of these episodes were found similar. This finding does not support the notion of "manic episodes are more frequent in women and depressive episodes are more frequent in men" (22). When current different findings were evaluated together, it can be suggested that biological mechanism which determines type and course of onset of disease and episode types is not affected by gender.…”
Section: Clinical Characteristicscontrasting
confidence: 56%
“…In women, positive linear correlation was found between age and 4th item of YMRS evaluating insomnia (r=0.28, p=0.01), age of onset and daily activities and hobbies (r=0. 22 th item of YMRS (r=0.35, p<0.01); negative linear correlation was found between age of onset of disease and total number of depressive episodes (r=-0.20, p=0.04), total number of hospitalizations (r=-0.21, p=0.03), stigmatization (r=-0.29, p<0.01), total number of episodes and daily activities and hobbies (r=-0.28, p<0.01), total number of manic episodes and sexual functionality (r=-0.26, p<0.01), relations with friends (r=-0.20, p=0.04), participation at social activities (r=-0.21, p=0.03), daily activities and hobbies (r=-0.25, p<0.01), total number of hospitalizations and daily activities and hobbies (r=-0.24, p=0.01), mean duration of hospital stay and 9 th item of YMRS evaluating destructive-hostile behavior (r=-0.21, p=0.02).…”
Section: Clinical Characteristicsmentioning
confidence: 99%
“…bkz., Beard, 1995;Pounder, 2000;Sadock, 2012;Kunduracı, 2013. Biçimbilimsel operasyonlara ait olan -(s)I ve -(n)In eklerinin eklenmesi hem öbeksel hem de anlamsal birleşimden (1.…”
Section: İyelik öBeklerinin Kuruluşu Ve çEkimlenişiunclassified
“…25 Bu çalışmadaki varsayıma göre, biçimbilimsel operasyonlar gerektiğinde sözdizimsel operasyonlardan önce, gerektiğinde sonra gerçekleşebilir. Özerk biçimbilim çerçevesinde, bileşenler arası etkileşime farklı yaklaşımlar için örneğin bkz., Zwicky, 1984;Beard, 1995;Sadock, 2012. Creole), iyelik öbeklerinin iki ögesinde de herhangi bir biçimbilimsel işaret yoktur; ait ve sahip ögeler sadece sözcük sırası sayesinde anlaşılır, bkz. (14) …”
Section: İyelik öBeklerinin Kuruluşu Ve çEkimlenişiunclassified
“…Carnap 1956, Hymes 1971, Karttunen 1974, Kasher 1972, Katz 1977, Keenan 1971, Kempson 1975, Lakoff 1972, Sadock 1974, Wilson 1975 …”
mentioning
confidence: 99%